2010
DOI: 10.1007/s00384-010-0941-6
|View full text |Cite
|
Sign up to set email alerts
|

Shortcomings in colonic stenting to palliate large bowel obstruction from extracolonic malignancies

Abstract: Our experience does not support the routine use of colonic stenting for extracolonic cancer obstructing the colon. A more realistic approach is necessary including either the acceptance that the obstruction represents a life-ending event or proceeding immediately to a colostomy. Decisions should be individualised and stenting used after recognising its shortcomings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…Compared with our previous result of an early success rate of 95.8% in patients with incurable CRC, 21 this study demonstrated a low clinical efficacy of SEMS in patients with ECM. Although the primary sites of ECM differed between the studies, 3,4 it is evident that the clinical efficacy of SEMS placement in patients with ECM was not as high as in those with CRC. The differences in clinical efficacy of SEMS placement between primary CRC and ECM may be attributable to the different characteristics of the tumors.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Compared with our previous result of an early success rate of 95.8% in patients with incurable CRC, 21 this study demonstrated a low clinical efficacy of SEMS in patients with ECM. Although the primary sites of ECM differed between the studies, 3,4 it is evident that the clinical efficacy of SEMS placement in patients with ECM was not as high as in those with CRC. The differences in clinical efficacy of SEMS placement between primary CRC and ECM may be attributable to the different characteristics of the tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Although meta-analyses demonstrated that technical and clinical success of SEMS as a palliative aim was 92% to 94% and 88% to 91%, respectively, in patients with CRC, 6,18,19 previous studies showed technical success rate of 42% to 66.7% and clinical success rates of 20% to 25% in patients with ECM. 3,4 One study argued that there was a 77% rate of clinical success in 35 patients with recurrent gynecologic cancer. 20 However, because 14 patients required subsequent surgery for continuous obstruction symptoms, the actual clinical success rate was 57%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although their effectiveness in the management of malignant colorectal obstruction secondary to colorectal cancer is documented, only a few studies have examined the efficacy of palliative stenting for extracolonic malignancies [13][14][15][16][17]. Few studies have compared the effectiveness of palliative SEMS placement for colorectal obstruction between colorectal cancer and extracolonic malignancies either [18,19].…”
mentioning
confidence: 99%